Immunotherapeutic approaches in EBV-associated nasopharyngeal carcinoma - Li, Wenting; Duan, Xiaobing; Chen, Xingxing; Zhan, Meixiao; Peng, Haichuan; Meng, Ya; Li, Xiaobin; Li, Xian-Yang; Pang, Guofu; Dou, Xiaohui (Frontiers in Immunology, 2023)
Epstein–Barr virus (EBV) was the first tumor virus in humans. Nasopharyngeal carcinoma (NPC) accounts for approximately 60% of the 200,000 new tumor cases caused by EBV infection worldwide each year. NPC has an insidious onset and is highly malignant, with more than 70% of patients having intermediate to advanced disease at the time of initial diagnosis, and is strongly implicated in epithelial cancers as well as malignant lymphoid and natural killer/T cell lymphomas. Over 90% of patients with confirmed undifferentiated NPC are infected with EBV. In recent decades, much progress has been made in understanding the molecular mechanisms of NPC and developing therapeutic approaches. Radiotherapy and chemotherapy are the main treatment options for NPC; however, they have a limited efficacy in patients with locally advanced or distant metastatic tumors. Tumor immunotherapy, including vaccination, adoptive cell therapy, and immune checkpoint blockade, represents a promising therapeutic approach for NPC. Significant breakthroughs have recently been made in the application of immunotherapy for patients with recurrent or metastatic NPC (RM-NPC), indicating a broad prospect for NPC immunotherapy. Here, we review important research findings regarding immunotherapy for NPC patients and provide insights for future research.